Cyclisation vs acylL migration OF α-allyl lactone dreived anion : Synthesis of spiro[4,5]dec-2-ene-1,6-diones - W. Jaivisuthunza (2018)
Directed by substituent R1, the α-allyl-γ-butyrolactone 9 either undergoes cyclisation to give the alcoholic cyclopentenone 12 or 1,2-acyl migration to give 13, when subjected to treatment with LDA in THF/TMEDA. An effective strategy to nullify this directive influence, and dictate cyclisation, is exemplified in a model synthesis of spiro[4,5]dec-2-ene-1,6-dione 19 by a one-pot tandem cyclisation - elimination process starting from 16. Copyright © 1996 Elsevier Science Ltd.